Testimonial Evidence. Perspectives and Confluences - Neculcea Marius; Ionescu Bogdan (Journal of Legal Studies, 2017)
The authors aim to “drill” into the complex issue of the testimonial evidence, through a fresher approach, thus being interested, besides the purely legal aspect, also in the historical, sociological and even psychological perspective.